Dysfunctions in Dopamine Systems and ADHD: Evidence From Animals and Modeling - Davide Viggiano; Daniela Vallone; Adolfo Sadile (Neural Plasticity)
Animal models are useful for characterizing neural substrates of neuropsychiatric disorders. Several models have been proposed for the study of Attention Deficit Hyperactivity Disorder (ADHD). The models can be divided into various groups: (i) genetically derived hyperactivity/ inattention, (ii) animal models showing symptoms after pharmacological intervention, and (iii) those based on spontaneous variations in a random population. Spontaneously hypertensive (SHR) and Naples High Excitability (NHE) rats show behavioral traits featuring the main aspects of ADHD in humans but show different changes in dopamine (DA) systems. In fact, the enzyme tyrosine hydroxylase is hyperexpressed in NHE rats and hypoexpressed in SHR. The DA transporter is hyperexpressed in both lines, although in the SHR, DAT activity is low (reduced DA uptake). The DA levels in the striatum and prefrontal cortex are increased in the juvenile SHR, but are decreased in handled young and non-handled older animals. The mRNA of the D1 DA receptor is upregulated in the prefrontal cortex of SHR and downregulated in NHE. The D2 DA receptors are likely to be hypofunctioning in SHR, although the experimental evidence is not univocal, whereas their mRNA is hyperexpressed in NHE. Thus, in SHR both the mesocortical and mesolimbic DA pathways appear to be involved, whereas in NHE only the mesocortical system. To understand the effects of methylphenidate, the elective ADHD drug treatment in humans, in a dysfunctioning DA system, we realized a simple mathematical model of DA regulation based on experimental data from electrophysiological, cyclic voltammetry, and microdialysis studies. This model allows the estimation of a higher firing frequency of DA neurons in SHR rats and suggests that methylphenidate increases attentive processes by regulating the firing rate of DA neurons.